2017
DOI: 10.1108/jgm-06-2016-0025
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking differences in psychological contracts of organizational and self-initiated expatriates

Abstract: Purpose Global staffing has remained a main focus within the field of international human resource management (IHRM) since the 1970s. However, research in the psychological contract (PC) of expatriates is limited. The purpose of this paper is to explore the differences in PC breach and violation for organisational expatriates and self-initiated expatriates (SIEs). Design/methodology/approach A survey questionnaire was developed covering 52 organisational expatriates and 119 SIEs from 35 countries/regions wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 55 publications
(110 reference statements)
0
27
1
Order By: Relevance
“…This study investigates differences between assigned expatriates (AEs), who are sent overseas by their home employer on a temporary basis to complete an international assignment, and self‐initiated expatriates (SIEs), who instigate their own relocation in a country of their choice to pursue cultural, personal, and career development opportunities, often with no definite time frame in mind (Doherty et al ., ; Andresen et al ., ). For years, and still today, many authors have called for the distinction between SIEs and AEs (e.g., Zhang and Rienties, ). Prior studies have shown that these two groups of IMEs are different along various dimensions (Shaffer et al ., ; Dickmann et al ., ) that might be grouped under three aspects: demographic characteristics, motivational drivers, and social support.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigates differences between assigned expatriates (AEs), who are sent overseas by their home employer on a temporary basis to complete an international assignment, and self‐initiated expatriates (SIEs), who instigate their own relocation in a country of their choice to pursue cultural, personal, and career development opportunities, often with no definite time frame in mind (Doherty et al ., ; Andresen et al ., ). For years, and still today, many authors have called for the distinction between SIEs and AEs (e.g., Zhang and Rienties, ). Prior studies have shown that these two groups of IMEs are different along various dimensions (Shaffer et al ., ; Dickmann et al ., ) that might be grouped under three aspects: demographic characteristics, motivational drivers, and social support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Workers with a rare expertise may be more likely to move to other countries offering better living and working conditions. In addition, compared to AEs, while SIEs have more choices of destinations, better interactions with locals, a longer foreign stay given their more successful adjustment from a cultural perspective, they receive less generous compensation arrangements and experience lower job satisfaction and a higher level of psychological contract breach and violation (Shaffer et al ., ; De Araujo et al ., ; Zhang and Rienties, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In line with previous studies (Peltokorpi and Froese, 2009; Richardson and Mallon, 2005; Zhang and Rienties, 2017), we made use of personal contacts, intermediaries and snowball sampling methods to collect data from LSEs and different policy actors across Germany. Of particular interest were sectors employing large numbers of LSEs, including healthcare, elderly care, food production and metal industries (Morse, 2015).…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…But, if we consider the needs of multi-directional knowledge flows in MNEs, staffing options with experiences in different nations may be more relevant, as they may bring social networks that enable such knowledge flows across borders. Indeed, staffing options with various international experiences have been acknowledged in more recent literature, such as inpatriation(Collings et al, 2010), SIEs(Andresen et al, 2013;Richardson and McKenna, 2014;Vaiman and Haslberger, 2013;Zhang and Rienties, 2017), global careerists…”
mentioning
confidence: 99%
“…But, if we consider the needs of multi-directional knowledge flows in MNEs, staffing options with experiences in different nations may be more relevant, as they may bring social networks that enable such knowledge flows across borders. Indeed, staffing options with various international experiences have been acknowledged in more recent literature, such as inpatriation (Collings et al, 2010), SIEs (Andresen et al, 2013;Richardson and McKenna, 2014;Vaiman and Haslberger, 2013;Zhang and Rienties, 2017), global careerists (Georgakakis et al, 2016), regional specialists (Sparrow et al, 2017). As these alternative staffing options have been studied separately without being integrated into subsidiary staffing research, it seems useful to develop a conceptual framework based on certain common dimensions in order to analyze and evaluate both traditional and alternative staffing options comprehensively.…”
mentioning
confidence: 99%